Daniel Tiger's neighborhood. ([s.l.] : Fred Rogers Company, 2013)
Four-year-old Daniel Tiger invites young viewers directly into his world, giving them a kid's eye view of his life and making them feel like one of his neighbors. As they follow Daniel's everyday adventures, preschoolers and their families learn fun and practical strategies and skills necessary for dealing with everyday experiences, like dealing with new experiences, taking turns with a favorite toy, and learning bathroom and daily routines.